2011
DOI: 10.1017/s000711451100479x
|View full text |Cite
|
Sign up to set email alerts
|

An α-lactalbumin-enriched and symbiotic-supplemented v. a standard infant formula: a multicentre, double-blind, randomised trial

Abstract: The aim of the present study was to evaluate the safety, tolerance and preventive effect on atopic dermatitis of an experimental a-lactalbumin-enriched and symbiotic-supplemented infant formula. A total of ninety-seven non-breastfed term neonates were enrolled into a double-blind, multicentre, randomised controlled trial in which they received experimental (n 48) or standard formula (n 49) for 6 months. The primary outcome was weight at 6 months of age. Secondary outcomes were gastrointestinal tolerance and ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
48
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 57 publications
(57 citation statements)
references
References 22 publications
1
48
0
1
Order By: Relevance
“…All but 2 studies included infants of both sexes, while Fomon et al [10] and Carnielli et al [11] enrolled male infants only. Ten of 14 studies aimed to investigate the suitability and safety of the formulae with a focus on protein and carbohydrate contents [2,10,12,13,14,15,16,17,18,19], while studies focused on fat composition aimed to investigate fat or mineral balances [11,20,21]. Schmelzle et al [17] and Lasekan et al [19] studied modified carbohydrate components in formulae.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…All but 2 studies included infants of both sexes, while Fomon et al [10] and Carnielli et al [11] enrolled male infants only. Ten of 14 studies aimed to investigate the suitability and safety of the formulae with a focus on protein and carbohydrate contents [2,10,12,13,14,15,16,17,18,19], while studies focused on fat composition aimed to investigate fat or mineral balances [11,20,21]. Schmelzle et al [17] and Lasekan et al [19] studied modified carbohydrate components in formulae.…”
Section: Resultsmentioning
confidence: 99%
“…The studies of Koo et al [20], Kennedy et al [21], and Carnielli et al [11] investigated formulae with modified fat contents. Most of the included studies focused on the protein component [2,10,12,13,14,15,16,17]. …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, probiotic supplementations were shown to impact the intestinal maturation as reported with Bifidobacterium lactis supplementation of preterm infants which induced the maturation of the intestinal IgAs response [97]. Likewise, in fullterm neonates an infant formula containing two strains of probiotics allowed the preservation of high SIgA levels at 6 months compared to the control group [98]. Furthermore, such supplementation was suggested to have a synergistic effect on gut humoral immunity at 12 months of age, since it has shown that significant higher level of total IgM, IgA, and IgG titers was detected in infants who had been breastfed exclusively for at least 3 months and supplemented with probiotics compared with those breastfed receiving placebo [99].…”
Section: Probiotics In Fullterm Neonatesmentioning
confidence: 91%
“…Discrepancies between the observed effects could be linked to the various probiotics strains used. Indeed, the mechanism of their action could be through the maturation of the immune system, as suggested by the study of Roze et al where low levels of IgAs in the control group has been associated with atopy [98].…”
Section: Probiotics In Fullterm Neonatesmentioning
confidence: 99%